Crafting dental specialities in Iran: insights from a qualitative study - Tayebe Rojhanian; Michael Aryan Kya; Shahram Yazdani; Mohammad-Pooyan Jadidfard (BMC Oral Health)
Abstract Background Different countries have varying dental specialities, shaped by diverse factors. The determinants influencing the development of these specialities differ between developed and developing countries. This study aimed to explore the factors contributing to the establishment of dental specialities in Iran, a developing country with a wide range of recognised dental specialities. Methods A qualitative case study was carried out, involving the review of 25 in-depth interviews and 47 documents. The data were organised using Atlas.ti (version 7.57) software and analysed through content analysis. This process included transcribing the interviews, identifying meaning units, abstracting content, categorising codes, and developing themes. Results The results identified three key factors influencing the development of dental specialities in Iran: stakeholders, contextual factors, and the specialisation process. Stakeholders encompass influential figures such as abroad-trained specialists, the government, the Ministry of Health and Medical Education, and scientific associations, along with their position, perceptions, and power. Contextual factors include cultural norms, sociopolitical relationships, political shifts, economic conditions, and academic disciplines. The process of establishing new dental specialities revealed several gaps, including the absence of formal needs assessments, advocacy plans, career planning, effective partnerships, and adequate evaluation mechanisms. Conclusion Contextual factors have played a crucial role in shaping dental specialisation in Iran, driving the formation of ideas in this field. Key players, including dentists trained abroad, have significantly influenced this process, often motivated by the desire to mirror practices in other countries. However, it did not address the specific oral health needs of the Iranian population. Due to limited awareness and the cost disparity between specialised and general services, there has been little public demand for dental specialisation. However, the process of establishing these specialities faces significant gaps that need to be addressed.